Level Knowledge Of Cataract, Education, And Sosioeconomic Status With Preoperative Visual Acuity In Patients With Senile Cataract In Phc Hospital Of Surabaya - Sumomba, Yordani; Ernawati, Titiek; Sustini, Florentina (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2019)
Introduction : Cataract is a cloudiness in the fibers or lens material inside the lens capsule. If the cataract was not treated immediately, the patient might experience blindness. Aim: This study aimed to analyze the correlation between the level of knowledge about cataract, education, and socioeconomic status with preoperative visual acuity in patients with senile cataract in hospital PHC Surabaya. Methods : This study was observational analytic with sampling through accidental sampling. The sample of the study was senile cataract patients preoperatively on August 24th to 27th September 2016. The variables of the study was the level of knowledge about cataract, education level, socioeconomic status, and preoperative visual acuity. Data analysis used Spearman correlation test. Results : Results obtained preoperatively senile cataract patients was highest in the age group 60-64 years (28%) and the lowest in the age group 75-79 years (6%). By gender, patients of senile cataract was highest in the group of male (52%) than female (48%). There was a significant correlation between the level of knowledge about cataract (p = 0.008) and level of education (p=0,006) with preoperative visual acuity in patients with senile cataract. There was no correlation between socioeconomic status with preoperative visual acuity in patients with senile cataract (p = 0.124). Conclusion : The results showed that the factors affecting patients in seeking treatment of cataract was the level of knowledge about cataract and level of education. Patients with a good level of knowledge and good education were expected to recognize the symptoms of cataracts immediately and could search for cataract treatment to prevent blindness.